Synthesis and Bioactivity of 3-(2,4-Dichlorophenyl)-5-(4-Hydroxy-3-Methoxyphenyl) Pyrazoline - Nurul Khotimah; Agung Rahmadani; Dewi Rahmawati; Mirhansyah Ardana (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2018)
Pyrazoline is a five-ring heterocyclic compound having 3 carbon atoms and 2 nitrogen atoms known to have some biological activity. This study aims to synthesize 3-(2,4-dichlorophenyl)-5-(4-hydroxy-3-methoxyphenyl) pyrazoline using 2’,4’-dichloro-4-hydroxy-3-methoxy chalcone and hydrazine. Synthesis was performed by reflux method at 80oC for 7 hours. The synthesis compounds were characterized by structural elucidation techniques. From the synthesis results obtained compound 3-(2,4-dichlorophenyl)-5-(4-hydroxy-3-methoxyphenyl) Pyrazoline is pale yellow powder with 84%yield. The result of antioxidant activity test by 2,2-diphenyl-1-picrylhydrazyl (DPPH) showed that the compound had very strong antioxidant activity, Antibacterial test by diffusion method to use paper disk showed that the compound had antibacterial activity against Gram positive bacteria (S.aureus) and Gram negative bacteria (E.coli) and toxicity test by Brine Shrimp Lethality Test (BSLT) showed that the compound had toxicity.